Vision-Enhancing Herbs from ancient Ayurveda text Bhava Prakash Nighantu: Scientific Appraisal on Natural Ocular Health Solutions - Maksane, Sushant; Mehar, Kapil (International Research Journal of Ayurveda & Yoga, 2025)
Ayurveda, the ancient science of life, holds a vast repository of medicinal knowledge, meticulously documented in classical texts such as Bhava Prakasha Nighantu. Among the numerous therapeutic categories described in this compendium, Chakshushya dravyas (ocular therapeutics) form a pivotal group, specifically targeting the prevention and management of ocular disorders. With the increasing prevalence of visual impairments caused by aging, environmental stress, and lifestyle factors, these time-tested remedies offer valuable insights into holistic ocular care. This review explores the extensive list of Chakshushya dravyas classified in Bhava Prakasha Nighantu, which includes herbs, minerals, animal-derived substances, and other formulations traditionally recommended for maintaining eye health. The plant-based remedies, categorized under Haritakyaadi, Karpooradi, Guduchyaadi, and Pushpa Vargas; exhibit antioxidant, anti-inflammatory; and rejuvenate properties, aiding in the prevention of oxidative stress-induced ocular degeneration and infections. Mineral-based substances from the Dhaatu Varga, such as Suvarna (Gold) and Yashada (Zinc), are noted for their contributions to retinal health and tissue repair. Animal derived products, including milk (Dugdha Varga) and ghee (Ghrita Varga), are revered for their nourishing and lubricating properties, effective in conditions like dry eye syndrome. In addition, formulations such as medicated oils (Taila Varga) and honey (Madhu Varga) are extensively utilized in traditional ocular therapies, including Anjana and Tarpana. While these remedies have been extensively employed in traditional medicine, modern pharmacological studies validate their efficacy. This integration of traditional wisdom with contemporary evidence highlights the relevance of Chakshushya dravyas in addressing the global burden of ocular diseases. However, further clinical trials and pharmacological investigations are imperative to standardize these remedies for broader applications.